An Absorption Capacity Investigation of New Absorbent Based On Polyurethane Foams and Rice Straw for Oil Spill Cleanup - Anh, Tuan Hoang; Van, Vang Le; M.Said Al-Tawaha, Abdel Rahman; Duong, Nam Nguyen; M.Said Al-Tawaha, Abdel Razzaq; M. M., Noor; Van, Viet Pham (Taylor & Francis, 2018)
Spilled oil has been considering as extremely serious disaster in the maritime field and oil exploration, and its effects lasted for decades, even hundreds of years. Oil spill treatment and recovery were the difficult and complicated issues due to the conditions of nature environment. In this work, rice straw- agricultural residue in Vietnam – with 205 k g/m3 of low density was filled in porous polyurethan matrix in fabrication process of absorbent. The experimental results about oil absorption capacity for this new absorbent material showed that, the absorbed oil mass in case of filling 25% of rice straw mass with 0.5 mm of size was highest, equal to 12.012 g oil/ g absorbent material after 120 minutes of treatment. The result of oil absorption capacity was around 3–4 times higher than that of material fabricated by pristine polyurethan or xenlulozo/lignocellulosic. Besides, fabrication process and SEM analysis were also experimentally carried out in this work.